Removal of Asphaltenes using Ionic Liquid-Effect of Ionic Liquid on Asphaltenes Characteristics - Farahnajwa Binti Amirrudin, Farahnajwa (Universiti Teknologi Petronas, 2009)
The objective of this project is to study the potential of ionic liquid in removing heavy, high molecular weight multi-ring aromatics, and/or resins, and/or polycyclic hetero atom - containing aromatics which is referred to collectively as asphaltenes from heavy hydrocarbon feed streams. The asphaltenes which interact with ionic liquid will be separated and removed from the remainder of the heavy hydrocarbon feed stream containing saturates (S), aromatics (A) and resin (R). The ionic liquid now saturated with the asphaltenes is expectantly be recovered by the addition of water for re-use. The first approach is to analyze the change of asphaltene average molecular weight after being contacted with ionic liquid. Second approach is to investigate asphaltene aggregate size, in case asphaltenes form agglomerate. Third approach is to examine the significant role of low boiling solvent such as water to recover and re-use ionic liquid saturated with asphaltene. The environment of this research also includes determining the characteristic change of the asphaltenes in term of elemental contents (C, H, and S), molecular weight and surface morphology. Two (2) types of commercial ionic liquid have been selected for the research work. To this end, it is expected that the content maltenes to increase while the content of asphaltenes to decrease